A new approach of under-frequency load shedding technique in an islanded distribution network - Karimi, M.; Mohamad, H.; Mokhlis, Hazlie; Bakar, A.H.A. (International Review of Electrical Engineering, 2012)
Under-frequency load shedding is a common technique to maintain the power system stability by removing the overload in some part of the system. The existing under-frequency load shedding schemes operate successfully in the interconnected grid system. A particular approach of under-frequency load shedding scheme is required for an islanded system which is known to be not as strong as the grid. This paper presents a new approach of load shedding scheme in an islanded distribution system incorporating distribution state estimation. The scheme is based on an intelligent technique to reduce the effect of power deficiency in an islanded network. The disturbance magnitude is calculated based on rate of change of frequency by using the simplest expression of the generator swing equation. Moreover, the process for assessing the power consumption of the customer can be achieved by state estimation method. In this paper, state estimation for a distribution network is developed and enhanced by composite load model to obtain the most practical value of the system state variables. Finally, the calculated value of the disturbance magnitude will be shed according to the estimated value of loads in each bus.